The EFFECT OF ANAGRAM GAME TO STUDENT VOCABULARY AT JUNIOR HIGH SCHOOL - Merinda, Merinda Bunga Anggresia; Hatip, Mochammad; Devanti, Yeni (ENJEL: English Journal of Education and Literature, 2024)
This research search is based on a preliminary study that I have researched about THE EFFECT OF ANAGRAM GAME TO STUDENT VOCABULARY AT JUNIOR HIGH SCHOOL. This study aims to determine the effectiveness of using the Anagram Game to improve vocabulary mastery of Grade 7 students at SMPN 02 Bondowoso in the 2022/2023 academic year. Researchers design grids that already exist in the curriculum, conduct treatments in class using anagram games, and provide questions so that we know the results that have been obtained when giving treatment to students. The research subject that I conducted was in grade 7 students at SMPN 02 Bondowoso, in the 2022/2023 academic year. The research that I did followed the existing procedures, namely planning in research, observing at school, conducting treatment, and collecting student data. To collect data, researchers used observation and test instruments. The data obtained is presented quantitatively. This study shows that Vocabulary Learning in the classroom with the Anagram Game method can increase students' vocabulary. This can be seen in the increase after each cycle. Prior to the research, none of the students scored above the KKM. In the first cycle, only a few students scored above the KKM. Whereas in the second cycle after conducting treatment using the Anagram Game, 14 out of 32 students scored above the KKM. That is, students give a positive response to the application of this method